Venezuelan International Meteorological and Hydrological Experiment (VIMHEX): hydrology report. v. 4, Soil temperatures and heat content - Stevens, M. A., author; Simons, Daryl B., author; Richardson, E. V. (Everett V.), 1924-, author; Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1971)
VIMHEX is an intensive program of tropical meteorological and hydrological observations taken in northeast Venezuela during the summer of 1969 to support a study of tropical atmospheric physics and the resulting effect of rainfall. The objectives of the program are to express the meso-scale weather structure in terms of the synoptic-scale envelope and to formulate the ground response to the rainfall produced by tropical weather disturbances over relatively flat tropical topography. During the period from 1800 hours on September 29 to 2400 hours on September 30, 1969, soil temperature and soil moisture content profiles were measured in the top 24 inches of the ground at the Anaco raingage site. From these data, the hourly heat content of the upper 24 inches of soil has been computed for the period. From 1800 hours on September 29 to 1000 hours on September 30, the heat loss from the upper 24 inches of soil was approximately 2 langleys per hour. In the next four hours, the soil gained energy at a rate of approximately 9 langleys per hour. Thereafter until midnight on September 30, content remained nearly constant. The maximum change in heat content was 22 langleys per hour between 1200 and 1300 hours on September 30. The night-time rate of decrease in soil thermal energy determined in this study agree closely with night-time long wave back radiation values reported by Renné (1970) for the same area.
Soil temperatures and heat content
CER70-71MAS-DBS-EVR-50.
November 1971.
Keywords: Soil temperature -- Venezuela